2014
DOI: 10.4141/cjps2013-146
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of rhizosphere organisms to enhance glomalin production and C sequestration: Pitfalls and promises

Abstract: rhizosphere organisms to enhance glomalin production and C-sequestration: Pitfalls and promises. Can. J. Plant Sci. 94: 1025Á1032. Arbuscular mycorrhizal fungi (AMF) reportedly produce glomalin, a glycoprotein that has the potential to increase soil carbon (C) and nitrogen (N) storage. We hypothesized that interactions between rhizosphere microorganisms, such as plant growth-promoting rhizobacteria (PGPR), and AMF, would influence glomalin production. Our objectives were to determine the effects of AMF/PGPR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…However, uncertainty remains as the AMF may have previously been present in our soil and contributed GRSP contents, but a general increasing trend of GRSP release over time indicates the effect of our induced inoculation treatments. Similar observations were reported by Walley et al [74] when they studied the effect of AM and plant growth-promoting rhizobacteria on glomalin production in un-sterilized soil. For EEG, the salinity showed no or little effect on natural glomalin present in the soil.…”
Section: Root Colonization Of Amf and Glomalin Production (Tg And Eeg)supporting
confidence: 88%
“…However, uncertainty remains as the AMF may have previously been present in our soil and contributed GRSP contents, but a general increasing trend of GRSP release over time indicates the effect of our induced inoculation treatments. Similar observations were reported by Walley et al [74] when they studied the effect of AM and plant growth-promoting rhizobacteria on glomalin production in un-sterilized soil. For EEG, the salinity showed no or little effect on natural glomalin present in the soil.…”
Section: Root Colonization Of Amf and Glomalin Production (Tg And Eeg)supporting
confidence: 88%
“…Cell walls of hyphal Arbuscular mycorrhizal fungi (AMF) produce glomalin and, death of hyphae deposited in the soil, further incorporated into soil organic matter (SOM) pool. Interaction of AMF and PGPR improved the glomalin production in rhizosphere of pea (Pisum sativum L.) and further enhanced C and N storage in rhizosphere (Walley et al, 2014). In boreal forest ecosystems root-associated fungi acts as organic decomposers and belowground mediators for C transport and respiration (Clemmensen et al, 2013).…”
Section: Pgpr and Carbon Sequestrationmentioning
confidence: 99%
“…About 60 g of sterilized and sieved sand was poured into 8 × 12 cm nylon bags (SEFAR NITEX, Filmar, Montreal, Quebec, QC, Canada) having 50 µm pores (Figure 1). This pore size was selected because it (1) minimizes sand contamination (inputs) and losses (outputs) during incubation and (2) allows soil microorganisms (fungal hyphae and bacteria) to colonize the sand bag [39], as GSRP is likely produced by those soil microorganisms [19]. Waterproof glue (LePage®), Mississauga, Ontario, Canada) was used to seal the bags (Figure 1).…”
Section: Sand Bag Preparationmentioning
confidence: 99%
“…However, several lines of evidence have brought a more nuanced definition and questions regarding even the glycoprotein nature of glomalin. For instance, glomalin was found to be co-extracted with humic substances [16][17][18] and, therefore, has a spectral signature more related to humic materials than to carbohydrates [19]. Based on this, Rillig [20] suggested that part of this operational pool of glomalin [termed as glomalin-related soil proteins (GRSP) and simply defined as any substance extracted by autoclaving soil in a citrate buffer and quantified using a colorimetric protein assay] may also come from general fungal hydrophobins (i.e., not necessarily of AM origin).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation